Journal Impact Factors for the year-after the next can be objectively predicted - Rocha-e-Silva,Mauricio (2016)
OBJECTIVE: To determine whether trends of Journal Impact factor variation can be objectively predicted for the year after next. METHOD: Curves for citations/document have been constructed for articles published in the two years previous to the current year (YEAR-1 and YEAR-2) and their citations in the current (unfinished year). Separate curves were constructed for YEAR-1 and YEAR-2. A parameter named INDEX R has been defined. INDEX R was calculated for a randomly selected sample of 100 journals with Impact Factors in the 1 - 3 range. RESULTS: INDEX R was found to distribute in a quasi-normal manner, with a borderline adherence to the Gauss distribution (0.10 > p > 0.05). A mean value of 0.60 ± 0.19 was observed. CONCLUSION: As a working hypothesis, it is suggested that INDEX R may indicate a trend for the Impact Factor to occur for the year-after (2017), to be published in the summer of 2018.